Frequency of perforations in endodontic treatment performed in patients treated in a university dental clinic in Ecuador, 2022 - Aguilar Romero , Gabriela Lisseth (2024)
Objectives: To determinate the frequency of perforations in the endodontic treatment performed in patients treated in a university dental clinic in Ecuador, 2022. Materials and Methods: A cross-sectional descriptive study was carried out with a simple random sampling, in 106 x-rays of patients between 20 and 50 years old. The frequency of drilling, the type of tooth, sex, age group and location of the lesion according to the root third were recorded. The chi square test was used to evaluate the relationship between the frequency of perforation and the other variables evaluated. Results: The frequency of perforations in endodontic treatment was 22.64%, being more common in incisor teeth represented by 29.31%, in female with 23.29%, in the age group between 20-34 years with 27.45% and in the apical third with 20.69% in the incisor teeth, there is no evidence of association with any of the variables reviewed. Conclusions: This type of injury affected a considerable number of patients, so stricter and more constant monitoring by supervisors is recommended to reduce the frequency of this type of iatrogenesis in the future.